Linkage studies and deletion screening in choroideremia. Issue 8 (August 1990) - Wright, A F; Nussbaum, R L; Bhattacharya, S S; Jay, M; Lesko, J G; Evans, H J; Jay, B
Abstract : Fourteen families with choroideremia (TCD) have been examined for linkage to nine genetic markers located on the proximal long arm of the X chromosome. Linkage to three markers (DXYS1, DXS72, DXS3) located in Xq21 was found with a four point lod score of 8.25. No evidence of submicroscopic deletions was observed using DXS233 and DXS232, both thought to lie within about 1 Mb of the TCD gene.